EFFICACY OF 5MG AND 10MG ROSUVASTATIN IN TYPE 2 DIABETES MELLITUS WITH YPERCHOLESTEROALEMIA - Ullah, Fahim; Aridi, Ayesha Khan; Rahim, Fawad; Rahman, Saddiq Ur; Ashfaq, Muhammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Coronary Heart Disease (CHD) is the most important complication and the leading cause of death in patients with type 2 diabetes mellitus (T2DM). Hypercholesterolemia is an important modifiable risk factor for CHD. Statins are the first line drugs for the treatment of hypercholesterolemia in DM. Comparative studies between different statins are available but different doses of the same statin have not been compared in our population. The objective of this study is to compare mean reduction in serum LDL-C level after using 5mg and 10mg of rosuvastatin among T2DM patients with hypercholesterolemia. This study will help finding lowest effective dose of rosuvastatin to achieve internationally set low density lipoprotein cholesterol (LDL-C) goals. Methods: A total of 82 patients with T2DM having fasting LDL-C levels equal or more than 100mg/dl were randomly allocated into two groups with 41 patients in each group. Baseline fasting serum LCL-C levels were obtained in all patients. Group A received 5mg while group B received 10mg of rosuvastatin daily at night. After 6 weeks, fasting LDL-C levels were obtained and analysed to compare the mean±SD reduction of LDL-C levels in both groups. Results: Baseline mean± SD LDL-C levels in group A and group B were 134.12±30.02 and 143.49±32.01 respectively (p 0.176). Follow up mean±SD LDL-C levels were 81.59±28.47 and 83.24±36.06respectively (p 0.818). Mean± SD reduction in LDL-C levels from baseline levels in group A and group B were 52.51±19.49 and 60.20±24.09 (p 0.116). Conclusion: Rosuvastatin 5mg is as effective as 10mg in reducing the LDL-C levels in type 2 diabetic patients with hypercholesterolemia.